(untitled) - Morling, Beth (New York, 2012)
Introduction to scientific reasoning; research foundations for any claim; tools for evaluating frequency claims, causal claims; balancing research priorities
Keywords: Psychology, Experimental,Tâm lý,Tâm lý, thực nghiệm,Psychology; Nghiên cứu,Phương pháp,Research,Methodology